Disparity Mapping of Rural-Urban High School Teachers' TPACK Level - Sari, Rima Meilita; Urfan, Faiz; Sahudra, Tengku Muhammad; Ridhwan, Ridhwan (Faculty of Geography, Universitas Gadjah Mada, 2025)
This study examines the disparity in Technological Pedagogical Content Knowledge (TPACK) levels among high school teachers, distinguishing between rural and urban settings within two regions on the Aceh East Coast, specifically Langsa City and Aceh Tamiang Regency. The research encompasses 560 teachers from both private and public high schools in Langsa City, an urban area, and Aceh Tamiang Regency, a rural area. Data is acquired through the test and questionnaire to capture teachers' TPACK levels. The data analysis used in this research is Global Moran's I and Anselin Local Moran's I to visualize patterns and disparities in teachers' TPACK levels. The research results reveal a significant disparity between urban (Langsa City) and rural (Aceh Tamiang Regency) areas. Langsa City has a random TPACK distribution pattern (Global Moran's I Index = 0,02438), while Aceh Tamiang Regency has a clustered pattern (Global Moran's I Index = 0,17018). This indicates that Aceh Tamiang Regency has higher disparities among high school teachers in TPACK levels compared to Langsa City. Then, Langsa City has better equality in the quality of high school teachers. Furthermore, analysis from Anselin's Local Moran's I reveals a concentration of teachers with the highest TPACK levels in the municipal district and teachers with low TPACK levels in the peripheral area. It can be found in both regions' hot and cold spots. Received: 2024-06-13 Revised: 2024-07-03 Accepted: 2025-06-26 Published: 2025-07-30